2009
DOI: 10.1007/s00360-009-0383-z
|View full text |Cite
|
Sign up to set email alerts
|

Digestive enzyme activities and gastrointestinal fermentation in wood-eating catfishes

Abstract: To determine what capabilities wood-eating and detritivorous catWshes have for the digestion of refractory polysaccharides with the aid of an endosymbiotic microbial community, the pH, redox potentials, concentrations of short-chain fatty acids (SCFAs), and the activity levels of 14 digestive enzymes were measured along the gastrointestinal (GI) tracts of three wood-eating taxa (Panaque cf. nigrolineatus "Marañon", Panaque nocturnus, and Hypostomus pyrineusi) and one detritivorous species (Pterygoplichthys dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 92 publications
3
71
1
Order By: Relevance
“…Second, isotopic incorporation appears to be primarily driven by catabolic tissue turnover in slowly growing adult fishes. And third, P. disjunctivus cannot assimilate carbon from the fibrous portions of detritus, and, consistent with its digestive physiology (German and Bittong 2009;German et al 2010), probably does not use recalcitrant polymers (e. g., cellulose) as a resource in the wild. Plasma solutes incorporated 13 C and 15 N more quickly than RBCs in P. disjunctivus.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Second, isotopic incorporation appears to be primarily driven by catabolic tissue turnover in slowly growing adult fishes. And third, P. disjunctivus cannot assimilate carbon from the fibrous portions of detritus, and, consistent with its digestive physiology (German and Bittong 2009;German et al 2010), probably does not use recalcitrant polymers (e. g., cellulose) as a resource in the wild. Plasma solutes incorporated 13 C and 15 N more quickly than RBCs in P. disjunctivus.…”
Section: Discussionmentioning
confidence: 85%
“…German (2009b) showed that neither P. disjunctivus nor Panaque nigrolineatus (a true wood-eating catfish) could assimilate significant amounts of organic matter (12.76% and 11.37%, respectively) or lignocellulose (32.08% and 23.69%, respectively) from a strictly wood diet in the laboratory, and both species lost weight when consuming solely wood. This inability to digest cellulose in their GI tracts comes from rapid gut transit (<4 h; German 2009b) and low cellulase activities (German and Bittong 2009). However, the fish are efficient at digesting soluble components of detritus (e.g., α-glucans, laminarin, β-glucosides, β-mannosides; German and Bittong 2009;German et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others authors [96] examined digestive enzyme activities, luminal carbohydrate profiles, and gastrointestinal fermentation in xylivorous and detritivorous loricariids catfishes to determine if these animals were capable of digesting a diet rich in refractory polysaccharides, and whether they were reliant on an endosymbiotic community to do so. The results showed that wood-eating catfishes are not reliant upon endosymbionts to digest refractory polysaccharides [96].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on other herbivorous fish have revealed the presence of a diverse hindgut microflora responsible for producing short chain fatty acids via fermentation, which are absorbed and metabolized by the fish [12,26]. However, comprehensive studies examining digestive enzyme activity levels, concentration of fermentative end-products, and gut transit time indicate that Panaque are detritivores and do not obtain energy directly from the digestion of wood [25,27], although the fish do swallow microbes associated with the wood and by-products generated by microbial wood degradation within the GI tract [28]. Thus, the Panaque GI tract provides an interesting environment-a vertebrate host GI tract enriched in cellulose and other recalcitrant wood compounds-offering an attractive system for discovery of new microbial species and novel enzymes.…”
Section: Introductionmentioning
confidence: 99%